Peran Guru Agama Dalam Menanamkan Moderasi Beragama - Samsul AR (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2020)
Islam encourages the followers to be moderate, belances, not extreme, and not inclusive. TheTawasuthis part of the moderation of religion that must be embededto the students so that students have a moderate attitude in thier life of the nation and state. In the middle of the advancement of the Indonesian nation, religious moderation is needed by all human being and its must be taught to students so that they can become peaceful, compassionate and tolerance people in the future. The involvement of religious teachers in providing understanding of the tawasuth for the students are needed in order that its can be habatuation in their life. The content of Islamic religious education is emphasized on the understanding of compassion, mutual love, mutual respect, and help each other in kindness. Because with this understanding, the students can implement it in their daily life. This paper explains the role of religious teacher in embeding religious moderation. This paper uses the library research method with a descriptive analysis approach.